STRATEGICALLY ORIENTED ENTERPRISE DEVELOPMENT MANAGEMENT - SHKURENKO, Olga; GAVRYSH, Olga; KALENSKA, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article substantiates the necessity of enterprise development management as an integral part of the overall strategy, emphasizing that future success depends on competitiveness, flexibility, and adaptability to market conditions. This necessitates the improvement of existing enterprise development management tools to ensure the alignment of strategic goals with operational processes, the influence of digitalization, human capital, and the ability to respond swiftly to changes. It has been proven that strategically oriented management enables enterprises to quickly react to market fluctuations, adjust their activities in response to emerging challenges, develop human capital, motivate employees, foster innovation, and establish a favorable corporate culture. The study outlines the relationship between strategic enterprise development management and planning. The integration of a strategic approach into enterprise management contributes to a comprehensive analysis of strengths and weaknesses in the context of competitive dynamics and stakeholder expectations. The article examines the industrial sector in Ukraine during 2022-2024, highlighting key determinants and conditions that drive change and development within enterprises. These include macroeconomic conditions, inflation rates, access to financing and investment, institutional reforms, infrastructure recovery, technological advancements, human capital, the expansion of international markets, integration into global supply chains, international financial aid, government support programs for businesses, and shifts in the global economy. A general framework for establishing a system of strategically oriented enterprise development management is proposed, outlining fundamental stages, principles, and types of management. In developing such a system, additional challenges must be considered, including globalization, digitalization, continuous technological advancement, and environmental risks.
Keywords: strategic management; development of the enterprise; strategy; process; challenges